Mexican experience on the design of catastrophic satellital parametric livestock insurances: conceptual and theoretical basis - Paz Pellat, Fernando; Bolaños, Martín; Pascual Ramírez, Fermín; Escamilla, Jesús; Cuesta, Mario; Zuñiga, José Inés (REVISTA TERRA LATINOAMERICANA, 2018)
The development of instruments for climate risk management allows implementation of actions to adapt to climate change as well to make eff icient use of f inancial resources to mitigate its impacts. In Mexico, the use of these instruments has not been documented. For this reason, this paper develops a conceptual-theoretical framework for instrumentation of remote sensing satellite parametric insurance to present its advantages and limitations in scope. To this end, the concept of risk unit, payment threshold and insurance-associated elements were applied to establish the climate risk associated with agricultural (livestock) activities, mainly drought. Under the critical requirement of a linear relationship between spectral index and the plant biomass without additive constant, an optimized NDVIcp spectral index was used, which resulted in the development of a technically sound insurance scheme that did not require historical information on livestock production. Moreover, it accurately reflects the reality in the f ield. Finally, the framework allowed setting the bases for designing catastrophic-type satellital parametric livestock insurance that is solid, transparent, and conceptually accessible to its users.